Valor de hiponatremia en la predicción de mortalidad intrahospitalaria en cirrosis hepática descompensada - Bazán Gallo, Carlos (2020)
Liver cirrhosis is a major health problem around the world, being one of the top ten causes of death. The presence of hyponatremia in cirrhotic patients has been associated with a poor prognosis for more than a decade. Recently, different better designed studies have shown that the presence of hyponatremia is associated with an increased risk of death in the short term (3 and 6 months).